The defensive behavioral patterns of captive white-lipped and collared peccary (Mammalia, Tayassuidae): an approach for conservation of the species - Nogueira, Selene S. C.; Reis, Aline M.; Marsaro, Stefane G.; Duarte, Jose M. B. [UNESP]; Moreto, Viviana; Lima, Stella G. C.; Costa, Thaise S. O.; Nogueira-Filho, Sergio L. G. (Springer, 2017)
Defensive behavioral patterns in response to human-induced rapid environmental change can affect animals' fitness and may play a role in species conservation status. To test this hypothesis, we compared the risk assessment and defensive behavioral responses of captive white-lipped peccary (WLP; Tayassu pecari) and collared peccary (CP; Pecari tajacu), which retain different conservation status; WLP are considered vulnerable and CP of least concern. We used an adapted paradigm of the mouse defense test battery (MDTB) comprising four consecutive tests. Two of these tests simulated a novel environment, while the other two stimulated the expression of defensive behavioral patterns. Besides differences in risk assessment and defensive threat/attack behavioral patterns between species, we compared flight initiation distance, flight speed, and plasma glucocorticoid concentrations. When facing a novel environment and risk challenges from humans' predator-like cues, the white-lipped peccary showed more exploratory and defensive threat/attack behavioral patterns, shorter flight initiation distances, and lower flight speeds, whereas the collared peccaries showed more cautious and retreat patterns, longer flight initiation distances, and higher flight speeds. There were also correlations between physiological and behavioral parameters. We confirmed our hypothesis that the collared peccary's cautiousness may help to prevent a decrease in its population, while the white-lipped peccary's exploratory and confrontational behavioral patterns in overhunted areas, together with other simultaneous factors as forest fragmentation, might contribute to placing this species in the vulnerable category.
Keywords: Behavioral plasticity; Defensive strategy; HIREC; Intra-specific variation; Risk assessment